2000
DOI: 10.1159/000018491
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and Echogenicity of the Skin in Children as Assessed by 20-MHz Ultrasound

Abstract: Background: Skin anatomy and physiology undergo modifications throughout the whole lifespan. In children the skin appears with structural characteristics, as evaluated by histology, which differ from those of adults, especially in the first years of life. Objective: The aim of our study was to evaluate skin thickness and echogenicity at different sites in children by 20-MHz ultrasound. Methods: Eight skin sites of 42 children and 30 young adults were studied with a 20-MHz B scanner. Skin thickness and mean ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 9 publications
8
76
2
4
Order By: Relevance
“…The wide range of differences in thickness and vascularization of human skin at different body sites (20,27) is likely a determinant in the ability of mosquitoes to obtain a blood meal and to transmit sporozoites at the different sites. Nevertheless, human skin is generally less than 2 mm thick (20), thus making it possible for the mosquito proboscis to penetrate below the skin at most body sites; this is even more likely in children, who tend to have thinner skin (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of differences in thickness and vascularization of human skin at different body sites (20,27) is likely a determinant in the ability of mosquitoes to obtain a blood meal and to transmit sporozoites at the different sites. Nevertheless, human skin is generally less than 2 mm thick (20), thus making it possible for the mosquito proboscis to penetrate below the skin at most body sites; this is even more likely in children, who tend to have thinner skin (20).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, human skin is generally less than 2 mm thick (20), thus making it possible for the mosquito proboscis to penetrate below the skin at most body sites; this is even more likely in children, who tend to have thinner skin (20). Differences in mosquito delivery of sporozoites to subcutaneous tissues with different degrees of vascularization, e.g., muscle versus adipose tissue, could also play a role in the dynamics of sporozoite transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this continuous state of development, the skin of children exhibits a pronounced susceptibility to various external and environmental factors, including inadequate skin care, water hardness or infant swimming practices [12,13]. This can lead to a perturbation of the fragile skin barrier homeostasis, resulting in a dry skin condition [9,13,14,15]. Previous studies investigating infants with healthy skin have suggested the use of emollients to increase SCH and thus support skin barrier maturation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, from studies in humans it is known that dermal echogenicity patterns changes with age [23], and the amount of subcutaneous fat as well as the skin can have an effect on echogenicity patterns of parenchymatous organs due to different ultrasound attenuation as shown for the pancreas [24]. Since animals scanned in this study differed by age (i.e.…”
Section: Discussionmentioning
confidence: 92%